Quantification of the usage of symptomatic treatment in patients suffering from multiple sclerosis. - Erélido Hernández Valero; Mikhail Benet Rodríguez (Medisur)
Background: Multiple sclerosis is a chronic demyelinated disease which constitutes de first cause of neurological handicaps in young adult patients and has no curative treatment. There are other options in which treatment of great importance can be applied for each of the so many symptoms that may appear. Objective: To show the insufficient utilization of symptomatic treatment in patients with multiple sclerosis. Methods: 47 patients were studied in a national consultation of multiple sclerosis in a two-year period. They were interviewed and examined. The data were collected in a survey and statistically processed opposing the specific signs and symptoms to the treatments used. Results: High percentages of patients with clinical manifestations and without the proper treatment for rigidity, weakness, ataxia, urinary retention and incontinence, sexual dysfunction, constipation, fatigue, pain and depression were found. Conclusions: It was already proved that there is an insufficient utilization of symptomatic treatment in patients suffering from multiple sclerosis.